Changes in the intestinal microbiota of broiler chicken induced by dietary supplementation of the diatomite-bentonite mixture - E. Węsierska; P. Micek; M. G. Adamski; K. Gondek; M. Lis; M. Trela; D. Wojtysiak; J. Kowal; A. Wyrobisz-Papiewska; G. Kunstman; S. Mosiołek; K. Smoroń (BMC Veterinary Research)
Abstract Background Diatomite is a source of biologically available silicon but in feed industry its insecticide and anti-caking properties have been also widely recognized. The aim of the study was to evaluate the effect of dietary diatomite-bentonite mixture (DBM) supplementation on the quantitative and qualitative composition of the bacterial microbiome of the broiler chicken gut. The trial was carried out on 960 Ross 308 broiler chickens divided into 2 experimental groups throughout the entire rearing period lasting 6 weeks. The birds were fed complete granulated diets without (group C) or with DBM (group E) in an amount of 1% from the 11 day of life. Two nutritionally balanced diets were used, tailored to the age of the broilers: a grower diet (from day 11 to 34) and a finisher diet (from day 35 to 42 of life). Results Diatomite used in a mixture with bentonite significantly altered the microbiome. Restricting the description to species that comprise a minimum of 1% of all analyzed sequences, 36 species in group E (with diatomite) and 30 species in group C (without diatomite) were selected. Several bacteria species were identified in intestinal contents of chickens for the first time. Thirteen species occurred only in group E: Agathobaculum butyriciproducens, Anaerobutyricum hallii, Anaerobutyricum soehngenii, Blautia producta ATCC 27,340 = DSM 2950, Gordonibacter pamelaeae 7-10-1-b, Helicobacter pullorum NCTC 12,824, Lactobacillus crispatus, L. helveticus DSM 20,075 = CGMCC 1.1877, Mucispirillum schaedleri, Phascolarctobacterium faecium, Phocaeicola coprocola DSM 17,136, P. massiliensis, and Ruthenibacterium lactatiformans. Conclusions The findings highlight the intricate and potentially consequential relationship between diet, specifically diatomite-bentonite mixture supplementation, and gut microbiota composition.